Evaluating the impact and clearance duration of freeway incidents - Haule, Henrick J.; Sando, Thobias; Lentz, Richard; Chuan, Ching-Hua; Alluri, Priyanka (International Journal of Transportation Science and Technology, 2019)
Transportation agencies use incident duration to report the performance of their incident management programs. Most agencies use the incident clearance duration, which in most cases refers to the duration from the reporting of an incident to the time the incident is cleared. This measure may not necessarily reflect how different types of incidents and various factors affect traffic conditions. The duration at which the incident influences traffic conditions could vary – shorter than the incident duration for some incidents and longer for others. This study, for the first time, introduced a performance measure called incident impact duration and demonstrated a method that was used for estimating it. Also, this study investigated the effects of using incident impact duration compared to the traditionally incident clearance duration in incident modeling. Using hazard-based models, the study analyzed factors that affect the estimated incident impact duration and the incident clearance duration. Results indicate that incidents detection methods, the number of responders, Traffic Management Center (TMC) operations, traffic conditions, towing and emergency services influence the duration of an incident. Moreover, the study assessed the predictive accuracy of the models resulted from both durations. It was observed that the incident impact duration provides a better prediction accuracy than the incident clearance duration.